Association of biophysical profile with neonatal outcome: an observational study - Singh, Gurmeet; Sood, Reena; Kaur, Karandeep (International Journal of Contemporary Pediatrics, 2017)
Background: Perinatal asphyxia is a common cause of neonatal mortality and morbidity in India. Antenatal surveillance prevents foetal injury and death and improves long term neurological outcome through optimal timing of delivery while avoiding unnecessary interventions such as caesarean delivery or preterm delivery. Methods: After thorough history and physical examination, all patients underwent BPP assessment with USG and electronic foetal heart rate tracing and association between BPP score and various parameters were studied. Results: Low BPP scores were associated with low Apgar score, increased rate of neonatal admissions and increased neonatal deaths. For BPP score of 6 there were 5 deaths constituting 71.4% of the total cases. Conclusions: BPP score was found to be significantly associated with Apgar score and neonatal outcomes.